Propagação de mirtileiro através de micro e miniestaquia - Pelizza, Tânia Regina (2009)
The present study aimed to group several aspects related to blueberry propagation (Vaccinium spp). Therefore, the trial was separated into five chapters. The first chapter investigated the ex vitro rooting of blueberry cultivars (Bluebelle, Woodard and Georgiagem) in the substrates (Plantmax®; Plantmax® + old saw (1:1); old saw; Plantmax® + vermiculite (1:1) and vermiculite. It was evaluated the percentage of rooting, callus formation, surviving explants, length and number of roots, length of the largest root, height of explants, number of shoots and total fresh mass. In the second chapter it was studied the process of acclimatization and growth of micropropagated blueberry plants cultivar Climax by using different substrates (carbonized rice hull + Húmus Fértil®, Plantmax® + vermiculite and soil + young saw of pinus) and two covering systems (with or without plastic covering on plants). The trial was assessed during 210 days. In this work it was evaluated the surviving percentage, increment of height, fresh and dry biomass of the aerial part and root of the plants. The third chapter investigates the microcuttings process of the blueberry Climax by comparing different substrates (Plantmax® + carbonized rice rusks (1:1); Húmus Fértil® and Vermicompound of cattle) and two types of microcuttings (median and apical). It was evaluated the rooting percentage, surviving, callus formation, number and length of roots, length of the largest root, number of leaves and shoots. The effect of phytorregulators Benzylaminopurine (BAP) and gibberellins (GA3) in different concentrations (control, 250mg/L of BAP, 250mg/L of BAP + 250mg/L of GA3) on growth of minicuttings O neal at five evaluations (0, 30, 60, 90 and 120 days) is assessed in the fourth chapter. It was measured: minicuttings height, number of leaves, number and mean length of lateral shoots. And, the fifth chapter evaluated the growth of micropropagated blueberry plants cultivar Georgiagem, using different concentrations of GA3 (0, 50, 100 and 150 mg/L) regarding period (0, 30 and 60 days). It was measured: plant height, number and mean length of shoots, fresh and dry biomass of aerial part and root. The best substrates for ex vitro rooting of blueberry explants were vermiculite and old saw. Among cultivars, Bluebelle and Woodard showed the greatest results. The substrate and covering system indicated for acclimatization and growth of blueberry plants Climax are Plantmax® + carbonized rice hull without plastic covering. Median microcuttings promoted better results for rooting of the blueberry Climax . The combination of Plantmax® + carbonized rice rusks is the best substrate for microcutting rooting of blueberry. The phytoregulators BAP + GA3 showed similar behavior to the control treatment regarding mean length of shoot and number of leaves. The growth in height and shoots number of the blueberry minicuttings O Neal increased by time and are independent of the use of phytoregulator. Blueberry plants Georgiagem positively responds to gibberellins action, mainly the aerial part of the plant. The concentration at 50mg L-1 de GA3 is sufficient to obtain blueberry plant response regarding growth.